2018
DOI: 10.1007/s11557-018-1415-4
|View full text |Cite
|
Sign up to set email alerts
|

ITS2 metabarcoding analysis complements lichen mycobiome diversity data

Abstract: Lichen thalli harbor complex fungal communities (mycobiomes) of species with divergent trophic and ecological strategies. The complexity and diversity of lichen mycobiomes are still largely unknown, despite surveys combining culture-based methods and high-throughput sequencing (HTS). The results of such surveys are strongly influenced by the barcode locus chosen, its sensitivity in discriminating taxa, and the depth to which public sequence repositories cover the phylogenetic spectrum of fungi. Here, we use HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 73 publications
(134 reference statements)
2
37
0
Order By: Relevance
“…For decades, studies dealing with phycobiont diversity in lichen thalli were primarily based on Sanger sequencing. In recent years, metabarcoding analyses have uncovered substantial species diversity associated with lichen symbioses 4 , 68 71 because HTS techniques detected a vast number of genotypes that would otherwise have remained undetected using conventional PCR amplifications. In fact, the discovery of phycobiont multiplicity within a single lichen thallus 38 , 39 , 41 , 72 and the exclusive use of Sanger sequencing in the majority of studies led the lichenologist community to consider whether terms such as specificity and selectivity (related to symbiotic association patterns) should be revised under this new perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, studies dealing with phycobiont diversity in lichen thalli were primarily based on Sanger sequencing. In recent years, metabarcoding analyses have uncovered substantial species diversity associated with lichen symbioses 4 , 68 71 because HTS techniques detected a vast number of genotypes that would otherwise have remained undetected using conventional PCR amplifications. In fact, the discovery of phycobiont multiplicity within a single lichen thallus 38 , 39 , 41 , 72 and the exclusive use of Sanger sequencing in the majority of studies led the lichenologist community to consider whether terms such as specificity and selectivity (related to symbiotic association patterns) should be revised under this new perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous works showed contrasting results when dealing with ITS1 or ITS2. While Blaalid et al 2013obtained similar results when using either ITS1 or ITS2 to perform fungal metabarcoding with environmental data, Banchi et al (2018b) showed discrepancies and biases in the detection of Basidiomycota when ITS1 or ITS2 were used as metabarcode for lichen mycobiomes, and suggested the complementary analysis of both ITS1 and ITS2 to reliably estimate the taxonomic diversity of the samples. In similar studies, Wang et al (2015) concluded conversely that ITS1 provides a better DNA barcode than ITS2 allowing a better species discrimination efficiency, whereas the ITS2 has been specifically selected and preferred to ITS1 in another study to catch fungal diversity in airborne samples (Banchi et al, 2018a).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 95%
“…With the dominance of Ascomycota and Basidiomycota in LAF and Alphaproteobacteria in bacterial communities across diverse lichen species, lichen-associated microbial compositions are known to be largely influenced by various environmental factors Bates et al, 2011;Cardinale et al, 2012;Hodkinson et al, 2012;U'Ren et al, 2012;Beck et al, 2014;Park et al, 2015Park et al, , 2016Wang et al, 2016). For example, lichenassociated fungal communities varied according to the host species (Beck et al, 2014;Park et al, 2015;Fernández-Mendoza et al, 2017;Banchi et al, 2018), climate conditions (U'Ren et al, 2012), seasonal changes of environmental conditions (Beck et al, 2014), geographic location, and altitude (Wang et al, 2016). Bacterial compositions in lichens were influenced by host species (Bates et al, 2011), age and sun exposure (Cardinale et al, 2012), substrate type and growth form (Park et al, 2016), and photoautotrophic symbiont and geography (Hodkinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%